SUICIDE ATTEMPTS REPORTED IN BRAZIL: AN EPIDEMIOLOGICAL ANALYSIS, 2010–2024 (CIPEEX, 2026)
Introduction: In Brazil, one person dies by suicide every 40 minutes. Suicide attempts represent the main factor associated with such deaths, and the epidemiological analysis of reported cases makes it possible to guide public policies, understand the scenario, and plan interventions. Objective: To analyze the epidemiological profile of suicide attempts reported in Brazil between 2010 and 2024, discussing implications for public mental health policies. Method: Observational, descriptive, and retrospective study, based on SINAN/DATASUS data on suicide attempts in Brazil between 2010 and 2024. Year, sex, age group, and case outcome were the variables analyzed, extracted through TabNet, tabulated in spreadsheets, and described by absolute and relative frequencies. Results: There was a significant increase in self-inflicted injuries in Brazil between 2010 and 2024, especially among females, with a continuous growth trend. The most affected age group was 20 to 29 years. Problems related to record completeness and improvements in data collection were observed, particularly in the “ignored/blank” category. This context reinforces the need for preventive actions in school and community environments. Conclusion: The analysis highlights the seriousness of suicide attempts in Brazil, especially among the female population and other vulnerable groups. The implementation of public policies is necessary, and the findings provide support for SUS strategies to reduce suicide mortality.
Keywords: Suicide, Attempted; Disease Notification; Epidemiologic Surveillance Services